2022
DOI: 10.21203/rs.3.rs-1404683/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global Carbon Inequality, 1990-2019: The Impact of Wealth Concentration on the Distribution of World Emissions

Abstract: This paper estimates the global inequality of individual greenhouse gas (GHG) emissions between 1990 and 2019, using a newly assembled dataset of income and wealth inequality and Environmental Input-Output tables. I find that the bottom half of the world population emits 12% of global emissions, while the top 10% emits 48% of the total. The global top 1% share in world emissions rose from 14% in 1990 to 17% in 2019. While two thirds of the inequality in individual emissions was due to inequalities between coun… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
(63 reference statements)
2
18
0
1
Order By: Relevance
“…The study also supports existing evidence on experiential inequalities regarding climate change (21). We found that eco-anxiety is higher among adolescents from less a uent families.…”
Section: Discussionsupporting
confidence: 90%
“…The study also supports existing evidence on experiential inequalities regarding climate change (21). We found that eco-anxiety is higher among adolescents from less a uent families.…”
Section: Discussionsupporting
confidence: 90%
“…Second, unsurprisingly, we observe that the households with the highest income level tend to also have the highest overall carbon footprints (Figure 2) (Chancel & Piketty, 2015; Ivanova & Wood, 2020; Otto et al., 2019). However, in contrast to findings from other countries such as China or the US (Jorgenson et al., 2017; Wiedenhofer et al., 2017), the emissions disparities among Japanese households are not very substantial between income groups.…”
Section: Discussionmentioning
confidence: 87%
“…Environmental deterioration, in particular, climate change and mounting income inequalities (Chancel and Piketty, 2015) are two key challenges for policy think-tanks in the decades to approach. The rapid economic growth of South Asia has brought about the rising scale of carbon emissions.…”
Section: Carbon Emissions Inequalities and Economic Freedom–selected ...mentioning
confidence: 99%
“…Different forms of “environmental inequalities” pertain to Chancel and Piketty (2015):Inequalities in revelation and contribution to pollutionInequalities by climatic policy-effects to modify the income spread, andInequalities in policy-making …”
Section: Carbon Emissions Inequalities and Economic Freedom–selected ...mentioning
confidence: 99%